Permissive Parenting and Juvenile Delinquency: Unveiling a Positive Link: Pengasuhan Permissif dan Kenakalan Remaja: Mengungkap Keterkaitan Positif - Putri, Lefiani Larasati; Laili, Nurfi (Indonesian Journal of Education Methods Development, 2023)
This study employs a quantitative approach to investigate the relationship between permissive parenting and juvenile delinquency. Conducted in Lemah Putro Village, with 110 subjects selected from a population of 150 through probability sampling, the research utilizes Pearson product moment correlation analysis via SPSS 23 for windows. The findings reveal a significant positive association (coefficient = 0.201, p = 0.027) between permissive parenting and juvenile delinquency, with a 4% influential contribution. This study underscores the impact of permissive parenting style on elevated levels of juvenile delinquency, highlighting the imperative for targeted intervention strategies. Highlights: Significant Positive Link: The study uncovers a substantial positive relationship between permissive parenting and juvenile delinquency. Quantitative Analysis: Utilizing Pearson correlation analysis, the research employs a robust quantitative approach to investigate the connection between parenting style and delinquency. Implication for Intervention: The findings emphasize the need for targeted intervention strategies to address the influence of permissive parenting on elevated levels of juvenile delinquency. Keywords: Permissive parenting, Juvenile delinquency, Relationship, Quantitative method, Intervention strategies.